Global metabolic changes induced by plant-derived pyrrolizidine alkaloids following a human poisoning outbreak and in a mouse model. Issue 6 (19th August 2016) - Robinson, Oliver; Toledano, Mireille B.; Sands, Caroline; Beckonert, Olaf; J. Want, Elizabeth; Goldin, Rob; Hauser, Michael L.; Fenwick, Alan; Thursz, Mark R.; Coen, Muireann
Graphical Abstract: Abstract: Several hundred cases of Hirmi Valley Liver Disease (HVLD), an often fatal liver injury, occurred from 2001 to 2011 in a cluster of rural villages in Tigray, Ethiopia. HVLD is principally caused by contamination of the food supply with plant derived pyrrolizidine alkaloids (PAs), with high exposure to the pesticide DDT among villagers increasing their susceptibility. In an untargeted global approach we aimed to identify metabolic changes induced by PA exposure through 1 H NMR spectroscopic based metabolic profiling. We analysed spectra acquired from urine collected from HVLD cases and controls and a murine model of PA exposure and PA/DDT co-exposure, using multivariate partial least squares discriminant analysis. In the human models we identified changes in urinary concentrations of tyrosine, pyruvate, bile acids, N -acetylglycoproteins, N -methylnicotinamide and formate, hippurate, p -cresol sulphate, p -hydroxybenzoate and 3-(3-hydroxyphenyl) propionic acid. Tyrosine and p -cresol sulphate were associated with both exposure and disease. Similar changes to tyrosine, one-carbon intermediates and microbial associated metabolites were observed in the mouse model, with tyrosine correlated with the extent of liver damage. These results provide mechanistic insight and implicate the gut microflora in the human response to challenge with toxins. Pathways identified here may be useful in translational research and as "exposome" signals.